2000
DOI: 10.1592/phco.20.19.1417.34865
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antipyretic Therapy on the Duration of Illness in Experimental Influenza A, Shigella sonnei, and Rickettsia rickettsii Infections

Abstract: Multivariate analysis suggested that antipyretic therapy prolonged illness in subjects infected with influenza A, but its use was the result of prolonged illness in those infected with S. sonnei. The precise nature of these relationships requires a prospective, randomized, placebo-controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

2005
2005
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 20 publications
1
39
0
2
Order By: Relevance
“…The results are consistent with other studies showing that antipyretic treatment increases viral shedding in human volunteers infected with rhinovirus [36] and lengthens the infectious period in children with chickenpox [37]. Moreover, in a study of human volunteers infected with influenza A, the number of antipyretic doses received was positively correlated with the duration of illness [38]. Some cytokines reduce viral shedding, so a likely mechanism by which antipyresis increases viral shedding is the suppression of temperature-dependent cytokine responses to influenza infection (see the electronic supplementary material, §3.2).…”
Section: Estimating the Effect For Influenzasupporting
confidence: 91%
“…The results are consistent with other studies showing that antipyretic treatment increases viral shedding in human volunteers infected with rhinovirus [36] and lengthens the infectious period in children with chickenpox [37]. Moreover, in a study of human volunteers infected with influenza A, the number of antipyretic doses received was positively correlated with the duration of illness [38]. Some cytokines reduce viral shedding, so a likely mechanism by which antipyresis increases viral shedding is the suppression of temperature-dependent cytokine responses to influenza infection (see the electronic supplementary material, §3.2).…”
Section: Estimating the Effect For Influenzasupporting
confidence: 91%
“…15 Data show beneficial effects on certain components of the immune system in fever, and limited data have revealed that fever actually helps the body recover more quickly from viral infections, although the fever may result in discomfort in children. 11,[16][17][18] Evidence is inconclusive as to whether treating with antipyretics, particularly ibuprofen alone or in combination with acetaminophen, increases the risks of complications with certain types of infections. 19,20 Potential benefits of fever reduction include relief of patient discomfort and reduction of insensible water loss, which may decrease the occurrence of dehydration.…”
Section: Physiology Of Fevermentioning
confidence: 99%
“…13 However, it is very important to point out that hyperthermia (as used here) differs in several important ways from an actual fever and that further study is needed to establish how activation thresholds are influenced during actual infections or tissue damage in which inflammatory signals may alter the signals that lymphocytes and other immune cells receive. Further study may lead to new strategies by which mild heating could be used therapeutically to improve pathologies, such as immunosenescence, that are linked to deficiencies in CD28 expression.…”
Section: Discussionmentioning
confidence: 99%
“…There is intriguing evidence that sustained increases in temperature associated with fever result in significant survival benefits following infection in multiple vertebrate species, 12 including humans. [13][14][15] Therefore, thermal shifts which exist during the early stages of infection, when optimal co-stimulatory signals may not yet be generated, might help to improve, or speed, the host immune response. While previous research on the relationship between physiological temperature shifts and specific T cell receptors during activation is sparse, several studies using non-specific activators point strongly to the hypothesis that thermal signals may help to calibrate the requirements for activation.…”
Section: Introductionmentioning
confidence: 99%